PENGARUH PENAMBAHAN KEMIRI (ALEURITES MOLUCCANA (L.) WILD) DAN VARIASI SUHU PENGERINGAN PADA SIFAT KIMIA DAN STABILITAS GULA SEMUT - Adi, Qadaruddin Fajri; Dinasti, Dika Ulfa; Adelina, Fitrah; Sudarmin, Sudarmin; Hasbiadi, Hasbiadi (AGROTEKSOS, Jurnal Ilmiah Ilmu Pertanian, 2024)
This study aims to ascertain how the stability and chemical characteristics of palm sugar are affected by the addition of hazelnuts and variations in drying temperature. This study applied a completely randomized design (CRD) with two factors and 3 replications. The first factor is the addition of hazelnut (K): K0 (0%), K1 (0.015%), K2 (0.03%). The second factor is drying temperature (S): S1 (50), S2 (75) and S3 (100). The parameters analyzed were moisture content, ash content, total sugar content and stability. The research data were processed using SPSS with ANOVA test method to see different levels of further testing with Duncan test method. The results showed that the addition of candlenut and variation of drying temperature had a very significant effect on moisture content and total sugar content, with the lowest moisture content of 0.67% and the highest total sugar content of 94.95% in treatment K1S3 (candlenut 0.015%, temperature 100). The results of the stability test showed that the product was stable and had no change in shape, taste, color and aroma from day 0 to day 28 at the use of temperature 100 °C (K1S3 and K2S3).